PERENCANAAN DAN PENJADWALAN PROYEK FABRIKASI DRYER 21M-362 MENGGUNAKAN METODE CPM DAN PERT DENGAN PROGRAM LINIER - Afan Avif Rahmatul Lailli (Universitas Muhammadiyah Gresik, 2022)
Completion of the project on time and according to the budgeted cost is not an easy task. The project planning and scheduling process determines whether or not the project is achieved against the requirements given by users. This study aims to analyze the trade-off between time and cost in the Dryer 21M-362 fabrication project carried out by Department Bengkel & Fabrikasi of PT Petrokimia Gresik with a completion time of 123 days from the normal time of 265 days. The Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) methods are used to analyze the critical path of activities in the project network and project life with a high probability using trial and error approach which is useful for simulating work acceleration logic, while for Linear Programming used to determine the most optimal project life. Initially the company had made its own schedule of activities at a cost of Rp. 1,273,314,964 with a project completion time of 123 days. Further analysis revealed that the shortest time to complete this project was 123 days with a total cost of IDR 1,162,853,872. this proves that the proper and appropriate scheduling of activities, the costs incurred will be lower by Rp.110,461,092.